Baraya Ngajaga Intervention: Promoting Bystander Behavior for Bullying Prevention Through Sundanese Cultural Values in Junior High School Students - Maslihah, Sri; Mudin, Muhammad Ilham; Nurendah, Gemala; Hidayat, Ghinaya Ummul Mukminin; Lestari, Selfiyani (Indonesian Psychological Research, 2026)
This study was conducted to develop and examine a bystander intervention programme integrated with Sundanese values for preventing bullying amongst junior high school students, namely the Baraya Ngajaga programme. The research utilized a quasi-experimental design employing One-Group Pretest-Posttest Design, which was carried out at SMPN X Bandung, Indonesia, involving ten female students aged 13-14 years from the school's "Agen Perubahan" community as the subjects. The intervention implemented was the "Baraya Ngajaga" programme delivered across three sessions, which combined Sundanese cultural values of Silih Asih, Sauyunan, and Ngamumule. Three instruments were employed to measure the program's effectiveness, namely the Conative Scale (α = 0.790) for behavioral intention, the Affective Scale (α = 0.810) for emotional reaction, and the Cognitive Scale (α = 0.733) for knowledge evaluation. The results showed enhancement in intervention intentions (p = 0.007), while emotional response and knowledge scores were not found to be significant.  Based on these findings, Baraya Ngajaga's pilot intervention showed promising initial results in increasing bystander intervention intentions through integrating local cultural values thus providing preliminary evidence for further development of anti-bullying programs tailored to local contexts.